2020
DOI: 10.1093/ecco-jcc/jjz203.695
|View full text |Cite
|
Sign up to set email alerts
|

P567 Impact of oral ferric maltol and IV iron on health-related quality of life in patients with iron deficiency anaemia and inflammatory bowel disease, and relationship with haemoglobin and serum iron

Abstract: Background Iron deficiency anaemia (IDA) is common in inflammatory bowel disease (IBD) and can significantly impair health-related quality of life (HRQoL). IV iron is currently the main treatment for patients intolerant or unsuitable for standard oral iron. Ferric maltol (FM), a stable oral complex of ferric iron and maltol, is designed to provide efficient iron delivery and minimise formation of free iron in the gut, thus reducing the potential for gastric adverse events. The HRQoL benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…The active-comparator trial of FM, AEGIS-H2H, was a prospective, multicenter, phase 3b, open-label, randomized, head-to-head trial comparing the efficacy and safety of FM and IV ferric carboxymaltose (FCM) for the treatment of IDA in 179 patients with IBD. [25][26][27] This noninferiority trial included adult patients with confirmed IBD and IDA (Hb = 8.0-11.0 g/dL for women, 8.0-12.0 g/dL for men and either ferritin <30 ng/mL or ferritin <100 ng/mL with TSAT <20%). Patients were randomized to FM 30 mg administered orally twice daily for 12 weeks or IV FCM administered according to manufacturer prescribing information.…”
Section: Aegis-h2h Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The active-comparator trial of FM, AEGIS-H2H, was a prospective, multicenter, phase 3b, open-label, randomized, head-to-head trial comparing the efficacy and safety of FM and IV ferric carboxymaltose (FCM) for the treatment of IDA in 179 patients with IBD. [25][26][27] This noninferiority trial included adult patients with confirmed IBD and IDA (Hb = 8.0-11.0 g/dL for women, 8.0-12.0 g/dL for men and either ferritin <30 ng/mL or ferritin <100 ng/mL with TSAT <20%). Patients were randomized to FM 30 mg administered orally twice daily for 12 weeks or IV FCM administered according to manufacturer prescribing information.…”
Section: Aegis-h2h Resultsmentioning
confidence: 99%
“…A recent post hoc analysis of the AEGIS H2H study published in abstract format examined the health-related quality of life benefits of FM and IV FCM. 27 The results showed non–statistically significant improvements in health-related quality of life scores (using SF-36) across all domains in both FM and IV FCM treated patients.…”
Section: Clinical Trialsmentioning
confidence: 86%
See 1 more Smart Citation
“…Oral iron is a cost-effective option and could temporarily replace intravenous iron in patients with anemia during COVID-19 pandemic [13]. We hypothesize that IBD patients with mild (10 g/dL < Hb < 13 g/dL) and moderate (8 g/dL < Hb < 10 g/dL) anemia may first undergo oral iron supplementation, preferably with ferric maltol, as post-marketing studies confirmed the effective and safe drug profile (Figure 1) [25][26][27]. In contrast, in patients who are unresponsive to oral therapy, or in those with severe anemia (Hb < 8 g/dL), the intravenous formulation should be considered and not delayed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 50% of the intravenous group patients lost at least one day of work, and 6.7% of them lost four-to-six working days, causing up to 775 € of daily losses per patient [25]. Interestingly, the physical component summary of the short form health survey (SF-36) and the mental component summary (MCS) values were slightly higher (p-value not significant) in patients treated with oral medication, suggesting a greater improvement in quality of life at the end of the study period [26]. In addition, total treatment costs per patient were lower in the oral drug group than in the intravenous arm (302.27 € vs. 489.37 €, respectively) [27].…”
Section: Ferric Maltolmentioning
confidence: 99%